Chasing Protection in Parkinson’s Disease: Does Exercise Reduce Risk and Progression? - Crotty, Grace F.; Schwarzschild, Michael A. (Frontiers in Aging Neuroscience, 2020)
Exercise may be the most commonly offered yet least consistently followed therapeutic advice for people with Parkinson’s disease (PD). Epidemiological studies of prospectively followed cohorts have shown a lower risk for later developing PD in healthy people who report moderate to high levels of physical activity, and slower rates of motor and nonmotor symptom progression in people with PD who report higher baseline physical activity. In animal models of PD, exercise can reduce inflammation, decrease α-synuclein expression, reduce mitochondrial dysfunction, and increase neurotrophic growth factor expression. Randomized controlled trials of exercise in PD have provided clear evidence for short-term benefits on many PD measurements scales, ranging from disease severity to quality of life. In this review, we present these convergent epidemiological and laboratory data with particular attention to translationally relevant features of exercise (e.g., intensity requirements, gender differences, associated biomarkers). In the context of these findings we will discuss clinical trial experience, design challenges, and emerging opportunities for determining whether exercise can prevent PD or slow its long-term progression.